Making an impact? The importance of aid effectiveness for charitable giving. A laboratory experiment. - Laura Metzger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
The question if private donors care about aid effectiveness when they donate to an international charity has received little attention in the literature on private charitable giving as well as in development microeconomics. This discussion is important, because a considerable share of foreign aid stems from private sources. Thus, individual donors can have an important influence on increasing social welfare by directing their funds to more effective organizations. We conducted a laboratory experiment to investigate if private donors want information about the exact Impact of their donation to an international charity before they donate, and how much they care about aid impact compared to other information: namely, information about administrations costs, and the recipient type benefiting from their donation. Our main results are the following. First, the demand was lowest for information about aid effectiveness, and highest for information about the recipient type. Second, donation levels were not significantly affected by differences in aid effectiveness, but were significantly affected by differences in administration costs, and recipient types. Participants in the administrations costs group used the additional information to punish the less preferred NGO by decreasing their transfers to zero. Participants in the recipient type group used the additional information to reward the preferred recipient type with higher-thanaverage transfers.
Keywords: D64; L31; O12; 330